2016
DOI: 10.1039/c5rp00102a
|View full text |Cite
|
Sign up to set email alerts
|

Developing critical thinking skills using the Science Writing Heuristic in the chemistry laboratory

Abstract: The Science Writing Heuristic (SWH) laboratory approach is a teaching and learning tool which combines writing, inquiry, collaboration and reflection, and provides scaffolding for the development of critical thinking skills. In this study, the California Critical Thinking Skills Test (CCTST) was used to measure the critical thinking skills of first year general chemistry students who were instructed using the SWH approach and first year general chemistry students who received traditional (TRAD) laboratory inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
102
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 23 publications
2
102
0
6
Order By: Relevance
“…In a seventh grade biology class, students who used the SWH performed better on conceptual questions, a textbook explanation, and revealed in interviews an understanding of scientific inquiry (Hand, Wallace, & Yang, ). Other studies have demonstrated the positive effect of SWH on students’ critical thinking skills (Quitadamo & Kurtz, ; Stephenson & Sadler‐Mcknight, ). Although the emphasis of SWH is on process skills, introductory students who used SWH outperformed their traditional counterparts on a conceptual assessment of the concept of chemical equilibrium (Greenbowe, Rudd, & Hand, ).…”
Section: Introductionmentioning
confidence: 90%
“…In a seventh grade biology class, students who used the SWH performed better on conceptual questions, a textbook explanation, and revealed in interviews an understanding of scientific inquiry (Hand, Wallace, & Yang, ). Other studies have demonstrated the positive effect of SWH on students’ critical thinking skills (Quitadamo & Kurtz, ; Stephenson & Sadler‐Mcknight, ). Although the emphasis of SWH is on process skills, introductory students who used SWH outperformed their traditional counterparts on a conceptual assessment of the concept of chemical equilibrium (Greenbowe, Rudd, & Hand, ).…”
Section: Introductionmentioning
confidence: 90%
“…Among these transferable skills is critical thinking (hereafter CT) (Stephenson & Sadler-McKnight, 2016). CT has been widely promoted over recent decades in higher education by many Asian countries such as Singapore and Malaysia (Luk & Lin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of critical thinking skills determines with the gain score <g> from Hake [17]. The difference enhancement of critical thinking skills between the experimental and control group, the calculation of t-test score was carried out, previously examined for the normality test using OneSample Kolmogorov Smirnov Test and the homogeneity test used Test of Homogeneity of Variances.…”
Section: Experimental Methodsmentioning
confidence: 99%